(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
To put an end to the controversy about the ideal human body, the content of the symmetry and size of the development of the human body was described. It is designed to improve the professional and theoretical training of a large number of specialists in physical culture and sports.